Voltage Stability Bifurcation Analysis for AC/DC Systems with VSC-HVDC. (31st March 2013) - Wei, Yanfang; Zheng, Zheng; Sun, Yonghui; Wei, Zhinong; Sun, Guoqiang
Abstract : A voltage stability bifurcation analysis approach for modeling AC/DC systems with VSC-HVDC is presented. The steady power model and control modes of VSC-HVDC are briefly presented firstly. Based on the steady model of VSC-HVDC, a new improved sequential iterative power flow algorithm is proposed. Then, by use of continuation power flow algorithm with the new sequential method, the voltage stability bifurcation of the system is discussed. The trace of the P-V curves and the computation of the saddle node bifurcation point of the system can be obtained. At last, the modified IEEE test systems are adopted to illustrate the effectiveness of the proposed method.